REHABILITATION OF NECK INJURY USING SHOCKWAVE THERAPY DURING REHABILITATION EXERCISES IN STUDENTS WITH NECK MUSCLE INJURIES IN GYMNASTICS - Asst. Lecturer. Atheer Fawaz karim (Scholars Digest Publishing, 2026)
The rehabilitation exercises developed by the researcher were accompanied by a shockwave device which aims to enhance the efficiency of the muscle. It includes exercises that aid in adjusting the neck movement, enhances muscle effectiveness, alleviates discomfort and enhances flexibility when combined with shockwave therapy. To determine the impact of a shockwave therapy-based rehabilitation program on pain level and function in students with neck muscle injury. It also investigated the impact of this intervention to improve neck muscle range of motion among injured participants. The research method was based on the characteristics of the phenomenon studied. Since the research problem and objectives are handled well using the experimental method, the experimental method was chosen. The sample of the research was deliberately selected, which is represented by students with neck muscle injuries from the Department of Physical Education and Sports Sciences at the Open Educational College, Al-Qadisiyah Center. In this case, the sample comprised seven male student only. The low effect of the present rehabilitation exercises was concluded by the realist researcher that the exercises prepared were efficient for reducing pain severity, increasing range of motion, and increasing muscular strength of injured gymnastics students.
Keywords: Shockwaves. Rehabilitation exercises. Pain.